LncRNA SNHG3: a potential biomarker for human diseases - Ren, Fu-Jia; Cai, Xiao-Yu; Yao, Yao; Fang, Guo-Ying (Frontiers in Cell and Developmental Biology, 2026)
With advancements in high-throughput sequencing and molecular biology technologies, the emerging significance of long non-coding RNAs (lncRNAs) in pathological conditions has been progressively unveiled. SNHG3, a member of the small nuclear RNA host gene (SNHG) family, is localized in both the nucleus and cytoplasm, and plays a pivotal role in multiple aspects of RNA metabolism, including transcription, splicing, translation and stability. Accumulating evidence indicates that SNHG3 is implicated in various human diseases, with a predominant focus on its oncogenic functions in different malignancies. Mechanistically, SNHG3 exerts its pathological functions by acting as a miRNA sponge, co-transcription factor or repressor, and stabilizer for oncogenic transcripts. Recent studies have further uncovered the essential role of SNHG3 in neurological disorders, such as brain injury, spinal cord injury, and drug-induced nerve injury. In this review, we comprehensively summarize the involvement of SNHG3 in various human diseases, and highlight its dual potential as a diagnostic and prognostic biomarker. Furthermore, we elucidate the regulatory mechanisms by which SNHG3 influences multiple RNA metabolism processes in related pathological processes, and propose its potential role in alternative splicing and the formation of cytoplasmic or nucleic ribonucleoprotein (RNP) granules.